Influence of δβ-thalassemia or regulatory elements in individuals with increased fetal Hb levels in the São Paulo northwest population - Carrocini, G. C S [UNESP]; Bonini-Domingos, C. R. [UNESP] (Genetics and Molecular Research, 2011)
Fetal hemoglobin (Hb F), formed by two alpha globin chains (α) and two gamma chains (γ) (α2 γ2), has reduced expression in adults, ranging from 0 to 1% of total hemoglobin. Increased levels of Hb F are due to mutations in the β-globin family, which cause hereditary persistence of fetal hemoglobin (HPFH) and delta-beta thalassemia (δβ-thalassemia).The control of the production takes place by the regulatory region and regions outside the β-globin family, among them 2q16, 6q23, 8q, and Xp22.2.The aims of this study were to determine the presence and frequency of two mutations for δβ-thalassemia, the XmnI polymorphism and β-globin haplotypes in healthy individuals with increased Hb F in the State of São Paulo. We analyzed 60 samples of peripheral blood of healthy adults, without complaints of anemia. The samples were separated into two groups according to Hb F level: group I - 34 samples with Hb F ranging from 2 to 15% and group II - 26 samples with Hb F over 15%. In relation to the polymorphisms examined, we found three heterozygous individuals (5%) for Spanish δβ-thalassemia, belonging to group I, whose Hb F levels were within the normal range.The Sicilian δβ-thalassemia mutation was not found, indicating the need to study other polymorphisms related to the increase of Hb F in adult life.The frequency of XmnI polymorphism was 33.3% and the mean Hb F levels were 15.48 ± 11.69%.The frequency observed in our study for this polymorphic site is higher than that found in the literature for healthy subjects.This polymorphism was more prevalent in individuals with Hb F levels below 15%. For four samples positive for this polymorphism, the Hb F levels were explained by the presence of HPFH and Spanish δβ-thalassemia mutations, so that the presence of the XmnI polymorphic site was not a determinant in the overexpression of γ-globin genes. Regarding β-globin haplotypes, 18 alleles and 27 distinct genotypic patterns were found.The pattern Atp1/Atp2 was the mostfrequent genotype (13.72%).Of the 18 alleles, 13 showed atypical patterns.The results show that the haplotype V was the most frequent (27.45%), followed by atypical Atp2 (13.72%) and Atp1 (11.76%), and that there was a higher correlation with the presence of HPFH and XmnI polymorphism.The high frequency of haplotype V in our samples and high frequency of atypical haplotypes may reflect a high rate of miscegenation in this population, suggesting an ethnic characteristic for the Brazilian population, requiring the evaluation of population genetic markers to corroborate this hypothesis. © FUNPEC-RP.
Keywords: β-globin haplotypes; δβ-thalassemia; Hb f; Xmni polymorphism; alpha globin; beta globin; gamma globin; hemoglobin F; blood sampling; Brazil; chromosome 2q; chromosome 6q; chromosome 8q; chromosome Xp; delta beta thalassemia; gene; gene frequency; gene mutation; gene overexpression; genetic polymorphism; genotype; haplotype; hemoglobin blood level; heterozygosity; human; population genetics; prevalence; protein expression; protein family; thalassemia; Xmn1 gene